Risk Assessment of Household Water Facilities Based on Physicochemical Water Quality and Sanitary Inspection in Urban Bengkulu, Indonesia - Riang Adeko; Moh.Gazali; Aplina Kartika Sari; Zainal Arifin (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
Safe household water should be acceptable, chemically stable, and protected from sanitary hazards to support urban public health. However, facilities in dense settlements remain vulnerable to contamination from wastewater, limited sanitation, groundwater dependence, and inadequate protection. This condition is evident in Bengkulu, where residents use piped water, dug wells, and bore wells with different vulnerability levels. Integrated assessment combining physicochemical measurement, sanitary inspection, and spatial mapping is needed to identify priorities. This study aimed to assess water-facility risk based on physicochemical water quality and sanitary inspection in Bengkulu. Sanitary risk was assessed using a standardized sanitary inspection checklist adapted from WHO-based household water facility inspection principles, and risk categories were determined from the cumulative sanitary hazard score. A quantitative cross-sectional study was conducted on 2,772 facilities. Data were analyzed using descriptive statistics, Kruskal–Wallis, Chi-square, Cramer’s V, Spearman correlation, ordinal logistic regression, and spatial mapping. Results showed that 60.89% were low risk, 31.64% medium risk, and 7.47% high risk. Dug wells showed higher risk, while odor, turbidity, facility type, and septic-tank distance were key determinants. Spatial mapping indicated that high-risk urban villages should be prioritized for sanitation improvement, monitoring, and interventions.